Fish leukocytes. Thematic bibliography - Ir. Hrytsynyak; T. Shvets (Ribogospodarsʹka Nauka Ukraïni, 2020)
Purpose. Forming a thematic bibliographic list of publications devoted to studies of leukocytes (white blood cells) of various fish species such as granulocytes, or granular leukocytes (neutrophils, eosinophils, basophils), and agranulocytes or agranular leukocytes (lymphocytes, monocytes).